The Correlation of Microclimate on Milk Productivity and Lactation Percentage of Friesian Holstein Dairy Cattle in Balai Pengembangan Ternak Sapi Perah Hijauan Pakan Ternak (BPTSP HPT) Cikole - Muhammad Dimas Rachmawanto; Afton Atabany; Bagus Priyo Purwanto (Faculty of Animal Science, Universitas Brawijaya, 2022)
External and internal factors can affect the body of livestock. External factors consist of climate, offering feed, and maintenance management. Internal factors include the biological aspects of lactating dairy. This research was conducted to see the microclimate relationship between milk production and the proportion of lactation. This study aims to identify and evaluate Friesian Holstein dairy cattle productivity based on the microclimate in BPTSP HPT Cikole. This study used the survey method to obtain secondary data. The regression and correlation test was used to analyze data. Results showed 111 Holstein dairy cattle productivity based on the amount of milk, and lactation proportion fluctuated from 2017 to 2019. The regression results and the impact of microclimate in general on milk production had no significant effect. It was proven that BPTSP HPT Cikole was successful in overcoming the effects of microclimate changes. In conclusion, that temperature, humidity, precipitation, and THI do not affect the production of Friesian Holstein cow's milk at BPTSP HPT Cikole. Based on the regression analysis results, precipitation significantly affects the proportion of lactation with an R2 value of 78.08%.